Perception of Psychiatry among Nursing Students in a public sector nursing school - Sarwat, Ayesha; Tauheed, Mohammad Moazzam; Ahmed, Sadaf; Sharafat, Shaheen (Journal of Pakistan Psychiatric Society, 2020)
Background: Generally under graduate nurses have a negative attitude towards mental health illness and thus avoid pursuing psychiatric nursing as their future career. Considering the important role of nurses in the multidisciplinary team required for mental health care in our country their education must be planned in a way to have a better perception and attitudinal change about psychiatric conditions Objective: To determine the attitude and perception among nursing students about psychiatry in a public sector hospital Methods: A cross sectional survey data was conducted from 31st January 2018 to 31st Jan 2019 at Institute of Nursing/DUH in Karachi. 236 nursing students were included. A semi structured questionnaire based on attitude to Psychiatry ( ATP) was used for data collection. The nursing students in the different training years were approached after their lectures. Descriptive statistics Results: the study showed that among N=236, the graduate nurses were 32.2% followed by 2nd year students (21.6%). Majority (70.3%) were belonged to age group 16-25 years. Gender distribution showed (58.9%) were females. Only 19.9% attended lectures on Psychiatry during their study. In ATP majority agreed that the overall merits have increased & it is a rapidly expanding frontier of medicine of Psychiatry. Regarding specific nursing school factors, they agreed that teaching about psychiatry should be part of curriculum. Have interest but were of opinion that no efforts are made to introduce it to postgraduate level. Conclusion: Student nurse are interested to continue it as a post graduate program and pursue as a career if provided adequate support. Thus existing psychiatry curriculum should be amended.. Keywords: under graduate, nursing students, Psychiatrist, mental illness